How to account for the possibility of disguise when assessing signature comparisons - Marquis, Raymond; Hicks, Tacha; Mazzella, Williams (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Following the recommendations of the ENFSI guideline for evaluative reporting, forensic handwriting examiners should assign a LR to evaluate their results. But when evaluating the results of a signature analysis, how should one account for the possibility of disguise? The present paper explores three possible solutions. The first option could be to assign two LR values, one assuming that the questioned signature was disguised, and the other that it was sincerely written. The authors show that this option is not optimal, since propositions ought to be exhaustive in the context of the case. It is the expert’s task to take into account all the relevant information to assess results in a meaningful way. The second option suggests partitioning the proposition of a genuine signature based on the event of disguise and non-disguise. This requires assigning probabilities of disguise and non-disguise and could impact the value of the results. The third option is to consider only the events that have an impact on the case and not formalising those that do not solely for the sake of exhaustiveness. These developments will hopefully help forensic handwriting examiners to cope with the possibility of disguise when assessing the value of signatures in casework.
Keywords: badanie pisma ręcznego; analiza sygnatur; interpretacja sądowa; współczynnik prawdopodobieństwa